PA01.35. To study the efficacy of Triphala kwath on Vyang Vyadhi [Chloasma] under the Siddhant of Aparkarshan Chikitsa Siddhant - Dharmik, Mrunal P. (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: APAKARSHAN CHIKITSA SIDDHANT: ‘Punarapi Apakarshan’ Ashtang Sangrah 12/6; ‘Apakarshan……’ Charak Viman 7/28. Vyanga Vyadhi Described under Kshudra Roga in various Samhita's. The objective is To study the sign & symptoms of Vyanga. To study the efficacy of Triphala Kwatha on vyanga under the siddhant Apakarshana chikitsa. METHOD: 30 patient were taken govt. Ayurved College, Nagpur, Dravyaguna OPD. Drug Triphala Kwatha for Virechanartha. Dose decided as per mrudu, madhyam, krura kostha. Duration: 1 to 2 months. Criteria of Assessment 30 patients were taken and chloasma was measured & scored (4 0) before treatment and after (1 &2 months) treatment. This data is presented in table. Following gradation were decided: 4 Very Severe dark circle; 3 Severe dark circle; 2 Moderate dark circle; 1 Mild dark circle; 0 Relived dark circle. The data is completely non parametric in nature and symptom severity is a desecrate variable. For coloration distribution is polynomial and so Wilcoxon Signed Rank Test was applied which is equivalent to paired “t test” of parametric analysis. RESULT: Details of statistical analysis of our data is presented below. Vyanga dark circle. Total score of Lakshana before starting the treatment = 89. After first Virechan Karma the total Lakshana score = 89 (0%). After Second Virechan Karma the total Lakshana score = 61(31.46%). After 7 days of second Virechan Karma the total Lakshana score = 61(31.46%) Mean observed second virechan karama as well as 7 days after second virechana karama = 2.0333. The S.D. of this data = 0.8087. Z= 5.112b. P. Value of this data (p < 0.05) CONCLUSION: The data shows significant (p < o.05); After Triphala Kwatha Virechan within 1 months p > 0.05; Triphala Kwatha Virechan after 2 month p < 0.05; Significant result found after 2 month.